Pengaruh Latihan Memukul Bola Digantung Terhadap Kemampuan Ketepatan Dan Kecepatan Smash Pada Siswa Ekstrakurikuler Bola Voli SMK Miftahul Ulum Sukorejo Pasuruan - Sulaiman, M.Adi; Pratama, Indra Gunawan (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
This study aims to analyze the effect of hanging punch training on smash ability and determine the results of this training. This research uses a quantitative type of research with a one group pretest-posttest experimental design method. The study's findings demonstrated that improving smash skill was significantly impacted by the hanging ball hitting training programme. Pretest accuracy measures yielded an average result of 13.80%, and pretest speed gave an average result of 15.10%. The posttest average resulted in 17.55% posttest precision and 14.00% posttest speed. The difference in average precision of 3.75% and speed - 1.1% faster - illustrate the significance of the change. After getting instruction in hitting hanging balls, student's ability to smash has increased, according to the analysis that was done. The influence for improving smash skill ranges significantly.